(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2017)
Literature regarding graduate student training suggests that graduate students struggle to become involved in academic publishing. Once involved in the publication process, however, graduate students are able to transform their learning, as well as develop knowledge and skills for their future careers. To help further foster student involvement in the publication process at the Werklund School of Education (WSE), the University of Calgary, seven graduate students from educational research and psychology decided to launch a student-run, peer-reviewed research journal called Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology (EPIGREP). Using Norris and Sawyer’s (2012) duo-ethnographic approach, this article focused on the editorial team members’ shared reflections and experiences as they answered questions regarding the identified gaps that EPIGREP would fill in terms of graduate student training, the challenges and barriers faced during the inaugural year, and the ways in which participation in the journal could empower journal users to engage in the publication process. Finally we noted implications and future directions regarding establishing EPIGREP as a graduate student initiative to foster research participation.